Identification and Characterization of the Sucrose Synthase 2 Gene (Sus2) in Durum Wheat - Volpicella, Mariateresa; Fanizza, Immacolata; Leoni, Claudia; Gadaleta, Agata; Nigro, Domenica; Gattulli, Bruno; Mangini, Giacomo; Blanco, Antonio; Ceci, Luigi R. (Frontiers in Plant Science, 2016)
Sucrose transport is the central system for the allocation of carbon resources in vascular plants. Sucrose synthase, which reversibly catalyzes sucrose synthesis and cleavage, represents a key enzyme in the control of the flow of carbon into starch biosynthesis. In the present study the genomic identification and characterization of the Sus2-2A and Sus2-2B genes coding for sucrose synthase in durum wheat (cultivars Ciccio and Svevo) is reported. The genes were analyzed for their expression in different tissues and at different seed maturation stages, in four tetraploid wheat genotypes (Svevo, Ciccio, Primadur and 5-BIL42). The activity of the encoded proteins was evaluated by specific activity assays on endosperm extracts and their structure established by modelling approaches. The combined results of SUS2 expression and activity levels were then considered in the light of their possible involvement in starch yield.